The Role of Therapy Education of Islamic Meaning to Overcome Global Human Crisis Today - Nina Aminah (International Journal of Nusantara Islam, 2015)
Modern community today showed the current issues that related to the complexity of personality. Islam offers a therapeutic meaning to overcome the global human crisis through the holy Quran. The aim of this study is to provide a qualitative analysis of logo therapy alternative to global human being who has experience critical conditions such as for someone who becomes the door of death (Sakarat al-Maut), acute illnesses, HIV Aids, kidney illness, stroke, coma, depression or stress, due to the hazards, and the other refractory diseases. Through the Quranic analytical perspective, the result of this study showed that the therapy of Islamic meaning based on the holy Quran can be seen as the broader and more comprehensive than the meaning therapy by Viktor E. Frank’s method.